Pengukuran Orientasi Pasar pada Jenis Usaha Mikro, Kecil, dan Menengah - Hidayat, Cecep (Bina Nusantara University, 2015)
The problem often faced in measuring market orientation of a business unit is to determine exact indicators of measurement. Small and medium-sized enterprises certainly have different characteristics that require appropriate indicators to measure market orientation. The objective in this study is to determine the dimensions and indicators for measuring market orientation in small and medium enterprise. To achieve the marketing objectives, marketing strategies are formulated that will adapt to internal and external environment. Strategic marketing is a marketing strategy based on market-driven. It means that the market needs is the basis of a marketing strategy. Research applied literature study with primary reference sources journal articles and books that discuss market orientation. Results of this literature study recommend that the dimension of the customer focus and competitor orientation is two dimensions that can be applied to measure market orientation for small and medium enterprises.